PENGGUNAAN MODEL GARIS BILANGAN VERTIKAL OLEH SISWA DALAM MENYELESAIKAN MASALAH KONTEKSTUAL - Fitri Samuntya; Fadhil Zil Ikram (SIGMA: JURNAL PENDIDIKAN MATEMATIKA, 2022)
Many teachers in Indonesia teach students horizontal number lines rather than vertical number lines. However, there are students who use vertical number lines to solve contextual problems that have never been taught in schools. Therefore, this study aims to find out why students use vertical number lines to solve contextual problems. This research is a qualitative research where data is collected by tests and interviews. The results showed that students used vertical number lines based on the context of the given questions.